Freedom as a Philosophical Problem - Nur S. Kirabaev; Alexander V. Khryachkov (RUDN Journal of Philosophy, 2025)
The research examines freedom as a philosophical problem. The philosophical understanding of freedom allows us to consider it as a speculative idea or an ideal construction underlying its numerous manifestations, as well as a life practice within the framework of social and spiritual life, including politics, religion and culture. It seems that the essence of freedom cannot be understood as a simple mechanical set of various and not always related, disparate ideas, points of view, teachings. It is important to keep in mind that multiple and different meanings of freedom are usually interconnected. The question of the nature of freedom is a question of its philosophical understanding. It is noted that freedom as a philosophical problem is not only a special value, spiritual quality, internal necessity, existential state, but also a concept that underlies its historical and metaphysical understanding. It is noted that the nature of human free will reflects both the internal spiritual state of a person and the reaction to the influence of external factors. Freedom as a value for which people go to death, personifies the highest human virtues, that is, freedom turns out to be the goal of human development. The philosophical foundations of freedom as an internal necessity “in the name of freedom” presuppose both a reflection of “responsibility” for freedom and an understanding of it as a special spiritual value. The historical practice of understanding freedom was based on the search for its nature in situations of choice of both overcoming necessity, on the one hand, and overcoming coercion, on the other. In addition, it was important to understand freedom as gaining independence and overcoming unfreedom. Therefore, civil liberties and human rights were of particular importance, as well as systems of governance for development, preserving individual freedoms and ensuring the well-being of society within the framework of a complex interaction between individual rights and group public interests. Social aspects of freedom clarify the role of cultural ideas in encouraging or hindering individual autonomy. Ethical connections between freedom and concepts of morality are noted. The interaction between moral obligations, social norms and individual behavior is considered in reasoning about the ethical consequences of freedom.